Changes in Vegetative and Reproductive Growth and Quality Parameters of Strawberry (Fragaria × ananassa Duch.) cv. Chandler Grown at Different Substrates. (15th June 2021) - Zahid, Noosheen; Maqbool, Mehdi; Hamid, Abdul; Shehzad, Muhammad; Tahir, Majid Mahmood; Mubeen, Khuram; Muhammad Rashad Javeed, Hafiz; Rehman, Haseeb Ur; Ali, Mazhar; Ali, Asgar; O'Reilly, Patrick; Shah, Syed Zulfiqar Ali
Abstract : Growth substrates (polyester wool, rice husk, and wheat straw), along with soil as control treatment, were compared for vegetative growth, yield, and quality of strawberry cv. Chandler. All growth substrates tested showed good results in terms of growth rate as compared with control. Strawberry plants grown in polyester wool showed the highest (89.50%) survival rate as compared to rice husk (70.50%), wheat straw (64.63%), and control (67.56%). Moreover, a significant increase was observed among number of flowers, fruits, and yield in plants grown in polyester wool. Besides, a significant high amount of total soluble solids (TSS) (12.38 ºBrix), titratable acidity (TA) (1.21%), ash (0.72%), vitamin C (37.39 mg/100 g), total carotenoids (3.90  µ g/100 g), and total anthocyanins (3.47 cyanidine-3-glucoside/100 g) was recorded in fruits grown in polyester wool as compared to control. From these results, it can be concluded that the use of polyester wool as a growth substrate for strawberries can give higher yield and better fruit quality.